Integration Strategy for Public Service Applications Based on Web Services (Case Study: BPOM and Ministry of Health) - Buhari Muslim (Green Publisher Indonesia, 2025)
Developing Web Service Based Public Service Application Integration is a Strategic Program of the POM Agency and the Ministry of Health in Accelerating Public Services to the Community, in the context of automating the delivery of data. Issuing Supervision Result Analysis Certificates (AHP) with Narcotics, Psychotropics and Precursor commodities (POM Agency) to the Ministry of Health to fulfill data needs in the import and export licensing services for Narcotics, Psychotropics and Pharmaceutical Precursors for business actors. The total number of AHP document requests (2021) was 730 documents and 615 documents were approved from Import and Export service performance data (SLA 2021). Web Service is software used in the data exchange process. The integration strategy carried out is to carry out comparative studies and analysis by conducting tests to determine which Web Service suits the application service needs, be it SOAP or REST. the data received is appropriate, valid and accurate with that in the database (S.Achsan 2022: 8). The final objective of this research is to conduct a comparative study and analysis to determine the appropriate web service, either SOAP or REST, by conducting local testing, to then be used in integrating the Ministry of Health's Monitoring Results Analysis Certificate (AHP)-NPP data safely, quickly and efficiently. from an SLA of 3 working days to 1-2 working days